SORPTION OF LANTHANIDES ON SMECTITE AND KAOLINITE - Coppin F.; Berger G.; Castet S.; Loubet M.; Bauer A. (My University, 2002)
Experiments were carried out to investigate the sorption of the complete lanthanide series (Ln or rare earth elements, REE) on a kaolinite and an a Na-montmorillonite at 22°C over a wide range of pH (3–9). Experiments were conducted at two ionic strengths, 0.025 and 0.5 M, using two different background electrolytes (NaNO3 or NaClO4) under atmospheric conditions or N2 flow (glove box). The REE sorption does not depend on the background electrolyte or the presence of dissolved CO2, but is controlled by the nature of the clay minerals, the pH and the ionic strength. At 0.5 M, both clay minerals exhibit the same pH dependence for the Ln sorption edge, with a large increase in the sorption coefficient (KD) above pH 5.5. At 0.025 M, the measured KD is influenced by the Cation Exchange Capacity (CEC) of the minerals. Two different behaviours are observed for smectite: between pH 3 and 6, the KD is weakly pH-dependent, while above pH 6, there is a slight decrease in log KD. This can be explained by a particular arrangement of the particles. For kaolinite, the sorption coefficient exhibits a linear increase with increasing pH over the studied pH range. A fractionation is observed that due to the selective sorption between the HREEs and the LREEs at high ionic strength, the heavy REE is being more sorbed than the light REE. These results can be interpreted in terms of the surface chemistry of clay minerals, where two types of surface charge are able to coexist: the permanent structural charge and the variable pH-dependent charge. The fractionation due to sorption observed at high ionic strength can be interpreted either because of a competition with sodium or because of the formation of inner-sphere complexes. Both processes could favour the sorption of HREEs according to the lanthanide contraction.